Microplastic particles are phagocytosed in gill cells of deep-sea and coastal mussels - Ikuta, Tetsuro; Tame, Akihiro; Takahashi, Tomoko; Nomaki, Hidetaka; Nakajima, Ryota (Frontiers in Marine Science, 2022)
It is becoming obvious that the abundance of microplastics is increasing in worldwide oceans, raising concerns about their impact on marine ecosystems. Tiny plastic particles enter the body of marine organisms not only via oral ingestion but also through the body surface (e.g., gills or epidermis), but the mechanism of internalization into cells is poorly understood. In this study, we conducted experiments using deep-sea chemosynthetic mussels with limited feeding by exposing their gills to fluorescently labeled microplastic beads. We identified the gill cell types that preferentially internalized the beads and demonstrated the inhibitory effect of phagocytosis inhibitors on bead uptake. Furthermore, using correlative light-electron microscopy, we microhistologically verified that beads were enclosed within membrane-bound vacuoles. Our results indicated that microplastic particles were internalized into gill cells of deep-sea and coastal mussels by phagocytosis. This study highlights the need for further research on plastic contamination via the body surface to conserve the highly endemic and vulnerable deep-sea fauna and mitigate human health risks from consuming coastal bivalves.